A Top-Down Optimization Methodology for Mutually Exclusive Applications. (17th February 2014) - Kilic, Alp; Marrakchi, Zied; Mehrez, Habib
Abstract : Proliferation of mutually exclusive applications on circuits and the higher cost of silicon make the resource sharing more and more important. The state-of-the-art synthesis tools may often be unsatisfactory. Their efficiency may depend on the hardware description style. Nevertheless, today, different applications in a circuit can be developed by different developers. This paper proposes an efficient method to improve resource sharing between mutually exclusive applications with no dependence on the coding style. It takes the advantage of the possibility of resource sharing as done in FPGA and of predefined multiple functions as in ASIC.